Green One-Pot Asymmetric Synthesis of Peptidomimetics via Sequential Organocatalyzed Aziridination and Passerini Multicomponent Reaction - dos Santos, Deborah A.; da Silva, Allan R.; Ellena, Javier; da Silva, Cecilia C. P.; Paixão, Marcio W.; Corrêa, Arlene G. (Synthesis, 2020)
Peptidomimetics containing an aziridine moiety have been reported as potent cysteine protease inhibitors. In this sense, the development of stereoselective and sustainable synthetic strategies to obtain three-membered N-heterocyclic compounds has gained importance in the last decades. In this work, an efficient method was designed to achieve highly functionalized aziridine peptidomimetics via a sequential reaction, which involves the organocatalytic aziridination of α,β-unsaturated aldehydes followed by the Passerini multicomponent reaction in an environmentally friendly solvent mixture (ethanol: water).
Keywords: peptidomimetics; green chemistry; organocatalysis; aziridine; multicomponent reaction